THE EFFECT OF FIRM CHARACTERISTICS AND EARNING MANAGEMENT TOWARD STOCK RETURN: BEFORE AND DURING PANDEMIC - Calvina Hartanto; Candy Candy; Robin Robin (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The main purpose of investors investing in the firm stocks is to achieve wealth growth through stock return. Stock return is one of the most important factors in choosing the best investments. This study investigates the relationship between firm characteristics and earning management on stock return before and during the pandemic and also when the periods are combined. It involves firms in the IDX Basic industry with the use of audited financial reports. The observation period is from 2016–2020 and using balanced panel data to produce generalizable results. For data analysis, we use the multiple regression method to prove the hypothesis and tested using the application of Stata. The results obtained from this study show that before pandemic, earning per share has negative effect on stock return. During pandemic, capital structure shows negative effect on stock return. While combining the period before and during the pandemic, firm size shows significant positive and earning per share shows significant negative on stock return.